2006
DOI: 10.4315/0362-028x-69.5.1096
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Selected Foodborne Pathogens on Poultry and Poultry Giblets from Small Retail Processing Operations in Trinidad

Abstract: We conducted a study to determine quantitatively and qualitatively the presence of Campylobacter spp., Escherichia coli, staphylococci, total coliforms, total aerobic bacteria, and Salmonella on broiler carcasses from selected small retail processors in Trinidad. We used standard media and procedures for detection and quantification. All carcass and weep samples were positive for aerobic bacteria, E. coli, total coliforms, and staphylococci. Significant differences in the mean counts of aerobic bacteria were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…There was no significant difference (P>0.05) between temperature of water ponds in Pond A1, A2, B1, and B2. This present study also observed study reported that chicken [25] and eggs [26] were potential agents for coliform. Thus, chicken offals and spoiled eggs introduced to the aquaculture system will increase coliform and reduce the hygiene level in the ponds.…”
Section: Temperature and Phsupporting
confidence: 86%
“…There was no significant difference (P>0.05) between temperature of water ponds in Pond A1, A2, B1, and B2. This present study also observed study reported that chicken [25] and eggs [26] were potential agents for coliform. Thus, chicken offals and spoiled eggs introduced to the aquaculture system will increase coliform and reduce the hygiene level in the ponds.…”
Section: Temperature and Phsupporting
confidence: 86%
“…The values of APC found in the product appear to be high in comparison with the other bacterial groups (Jay 2002); yet, there is a limited knowledge of the average APC for giblets products due to the lack of regular microbial testing of this product. Our results fall in the range of APC and E. coli counts found by Rodrigo et al. (2006) from naturally contaminated chicken livers from Trinidad.…”
Section: Discussionsupporting
confidence: 57%
“…For instance, Salmonella serotype Enteritidis has been associated with human disease by the consumption of improperly cooked poultry giblets (Anon 1984; Plummer et al. 1995; Rodrigo et al. 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it also may serve as a vehicle of foodborne pathogens, such as Campylobacter and Salmonella (Dufrenne et al, 2001;Zhao et al, 2001;Dominguez et al, 2002;Wilson 2002;Burgess et al, 2005;Meldrum et al, 2005Meldrum et al, , 2006Rodrigo et al, 2006;Meldrum and Wilson, 2007;Trajkovic-Pavlovic et al, 2007;Vindigni et al, 2007). Similarly, we and others have hypothesized that retail poultry may be a foodborne reservoir of ExPEC causing such conditions as UTIs, meningitis, and sepsis of human beings ( Johnson et al, , 2007aRodriguez-Siek et al, 2005a;Manges et al, 2007).…”
Section: Discussionmentioning
confidence: 99%